Correlação entre evapotranspiração e evaporação - Bernardo, Salassier; Fonseca Homem, Antônio Cloves (Revista Ceres, 2025)
This study was concerned with the determination of evapo- transpiration by three methods; evaporation pan (U.S. W.B. Class A Pan), Blaney-Criddle equation and the Piche evaporimeter at seven location in the State of Minas Gerais (Lavras, Juiz de Fora, Viçosa, Governador Valadares, Barbacena, Montes Claros e Poços de Caldas) and one in the state of Espirito Santo (Vitoria).